Screening young athletes for diseases at risk of sudden cardiac death: role of stress testing for ventricular arrhythmias. (February 2020) - Zorzi, Alessandro; Vessella, Teresina; De Lazzari, Manuel; Cipriani, Alberto; Menegon, Vittoria; Sarto, Gianmarco; Spagnol, Rachele; Merlo, Laura; Pegoraro, Cinzia; Marra, Martina Perazzolo; Corrado, Domenico; Sarto, Patrizio
Aims: The athletic preparticipation evaluation (PPE) protocol proposed byt he European Society of Cardiology includes history, physical examination and resting electrocardiogram (ECG). The aim of this study was to assess the results of adding constant-load ECG stress testing (EST) to the protocol for the evaluation of ventricular arrhythmias (VA) inducibility. Methods: We evaluated a consecutive cohort of young athletes with history, physical examination, resting ECG and EST. Athletes with VA induced by EST underwent 24-hour 12-lead Holter monitoring and echocardiography. Cardiac magnetic resonance (CMR) was reserved for those with frequent, repetitive or exercise-worsened VA, and for athletes with echocardiographic abnormalities. Results: Of 10, 985 athletes (median age 15 years, 66% males), 451 (4.1%) had an abnormal history, physical examination or resting ECG and 31 (0.28%) were diagnosed with a cardiac disease and were at risk of sudden cardiac death. Among the remaining 10, 534 athletes, VA at EST occurred in 524 (5.0%) and a previously missed at-risk condition was identified in 23 (0.22%); the most common ( N = 10) was an echocardiographically silent non-ischaemic left-ventricular fibrosis evidenced by CMR. The addition of EST increased the diagnostic yield of PPE by 75% (from 0.28% to 0.49%) and decreased the positive predictive value by 20% (from 6.9% to 5.5%). During a 32 ± 21 months follow-up, no cardiac arrests occurred among either eligible athletes or non-eligible athletes with cardiovascular disease. Conclusions: The addition of exercise testing for the evaluation of VA inducibility to history, physical examination and ECG resulted in an increase of the diagnostic yield of PPE at the expense of an increase in false-positive findings.